2009
DOI: 10.1007/s11746-009-1487-z
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Removal from Squid Liver Oil by Crosslinked β‐Cyclodextrin

Abstract: The present study was designed to optimize the different conditions for b-cyclodextrin (b-CD) crosslinked by adipic acid on cholesterol removal from squid liver oil. Different factors were concentrations of crosslinked b-CD, mixing temperature, ratio of squid liver oil to distilled water, mixing time and mixing speed. It was found that cholesterol removal from squid liver oil was significantly affected by concentrations of crosslinked b-CD, mixing temperature, ratio of squid liver oil to distilled water, mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…According to Lee et al [14] evaluating the optimum concentration of crosslinked b-CD for cholesterol removal from squid liver oil, the optimum concentration of crosslinked b-CD was 25% (w/v). Other studies using digitonin [26] and saponin [27] for cholesterol adsorption indicated that above certain concentrations, saponin and digitonin showed a decrease in cholesterol removal from milk and butter oil, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Lee et al [14] evaluating the optimum concentration of crosslinked b-CD for cholesterol removal from squid liver oil, the optimum concentration of crosslinked b-CD was 25% (w/v). Other studies using digitonin [26] and saponin [27] for cholesterol adsorption indicated that above certain concentrations, saponin and digitonin showed a decrease in cholesterol removal from milk and butter oil, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The range of cholesterol (73.38-85.60%) was removed from cod liver oil by mixing with crosslinked b-CD (15-25%, w/v) at 50°C for 20 min. In our laboratory, several studies on the cholesterol removal from different food products including squid liver oil [14], egg yolk [15], cream [16], lard [17], and milk [18] by crosslinked b-CD have been performed. In squid liver oil, the range of 80.04-87.08% cholesterol was removed by mixing with crosslinked b-CD (15-25%, w/v) at 55°C for 20 min [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2005), ice cream (Ha et al. , 2009), squid liver oil (Lee et al. , 2010) and cod liver oil (Chang et al.…”
Section: Introductionmentioning
confidence: 99%